Sexual transmission of zika virus - Passos, Mauro Romero Leal; Miranda, Angelica Espinosa (Brazilian Journal of Sexually Transmitted Diseases, 2022)
From time to time, the world experiences challenges related to human health. Many of these problems first affect small populations in specific regions of the planet. Depending on the characteristics of the problem, the situation can spread all over the world. This is especially true in the current century with the huge frequency and speed of movement of people and cargo that may carry, unintentionally but effectively, vectors’ agents and/or infectious disease originators. It is evident that upon arrival to a new region of the planet, the vectors’ agents need favorable conditions to remain viable to new infections. In a new situation, the issue of reducing spread of an emerging infectious disease is aggravated when, in addition to the speed of geographic expansion described earlier, there is a lack of knowledge by the scientific community of aspects of transmission, physiopathology, diagnosis, and treatment. [...]